Examining the Evidence: Graduate Employability at Nelson Mandela Metropolitan University - Nel, Heather; Neale-Shutte, Marian (South African Journal of Higher Education, 2016)
Globally there is increasing pressure on higher education to enhance the employability of graduates by ensuring that university learning experiences contribute to inculcating the knowledge, skills and attributes that will enable graduates to perform successfully as citizens in the knowledge economy. Graduate employability is evidenced in a mix of personal attributes, understandings, skilful practices, and the ability to reflect productively on experience. This paper will provide an analysis of survey research conducted at Nelson Mandela Metropolitan University (NMMU) to investigate graduates’ perceptions of the extent to which their particular university qualification contributed to employability. The research was conducted by means of a structured questionnaire survey administered among NMMU graduates at graduation ceremonies in April 2011, with an online follow-up questionnaire administered two months later. Of a total of 5397 graduates, 2379 completed the questionnaires resulting in a response rate of 44.1 percent. The overwhelming majority of respondents reported that their qualifications and study experiences at NMMU had enhanced their employability and this was supported by the research findings which demonstrated that 68 percent of all respondents had secured employment at the time of graduation. Respondents recommended various courses of action to further enhance graduate employability, including increased exposure to work-integrated or experiential learning and improved relations between university academics and employers. The study revealed that the purposeful design and delivery of curricula and co-curricular activities support the development of intellectual and interpersonal skills that enable graduates to fulfil a role, rather than merely possessing the immediate task-related skills that enable them to perform a specific job.